Assessing the level of market orientation at Qazvin teaching and medical hospitals: Application of the three-dimensional market analysis model - Fateme Vahdati; Mohammadreza Mohammadkhani; Omid Khosravizadeh; Rana Soheylirad; Sogol Sarikhani; Bahman Ahadinezhad (Tehran University of Medical Sciences, 2020)
Background: In addition to providing effective and equitable services to low-income groups, teaching hospitals must obtain a significant share of the demand of high-income groups in order to have a balanced and positive operational performance. The aim of this study was to investigate the market orientation of teaching and medical hospitals in Qazvin. Materials & Methods: This descriptive-analytical study was conducted at teaching and medical hospitals of Qazvin University of Medical Sciences in a cross-sectional manner in 2020. Data were collected in a one-month period through a questionnaire survey. The study population was the total staff working in 6 hospitals of this university who were selected using quota-random sampling method. The required data were obtained by collecting 411 market orientation questionnaires (Ahmad and Eqbal 2013) and were analyzed in SPSS 16 software. One-way analysis of variance with 95% confidence interval was used to compare the means. Results: The market orientation of all studied hospitals was 2.88 out of 5. Also, customer orientation had the highest average (3.32 out of 5) and paying attention to competitors had the lowest average (2.80 out of 5). The mean for dimension of coordination between tasks was 2.86 out of 5. Apart from paying attention to competitors, there was a statistically significant difference in terms of market orientation, customer orientation and coordination between tasks(P <0.05). Conclusion: The status of the studied hospitals were in medium, high and below the average in terms of market orientation, customer orientation and attention to the competitor, respectively. To achieve a profitable service market, hospitals must implement a strategic plan against competitors and direct staff duties to strengthen market orientation.